O норме разложимых подгрупп в локально конечных группах - Лиман, Ф.Н.; Лукашова, Т.Д. (Український математичний журнал, 2015)
Розглядаються взаємозв'язки між нормою розкладних підгруп та нормою абелевих нециклічних підгруп у класі локально скінченних груп. Також встановлено деякі властивості періодичних локально нільпотентних груп з недедекіндовою нормою розкладних підгруп. We study the relationships between the norm of decomposable subgroups and the norm of Abelian noncyclic subgroups in the class of locally finite groups. We also describe some properties of periodic locally nilpotent groups in which the norm of decomposable subgroups is a non-Dedekind norm.